PENGARUH PRICE TO EARNINGS RATIO, DEBT TO EQUITY RATIO, RETURN ON ASSET DAN PRICE TO BOOK VALUE TERHADAP HARGA PASAR SAHAM - STELLA STELLA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2009)
The objective of this research is to find out the influence of internal fundamental variables on the stock market price. Internal fundamental variables in this research are Price to Earnings Ratio (PER), Debt to Equity Ratio (DER), Return on Assets (ROA) and Price to Book Value (PBV). Data for this research are stocks closing price in the stock exchange, the PER, DER, ROA and PBV of 14 stocks of LQ45 from 1st quarter in 2002 to 4th quarter in 2006. These data are tested with Panel Data Regression Model. The result of study shows that the PER, DER and PBV have significant influence on the stock market price, but the ROA has not influence on the stock market price.